Perbandingan Model Pembelajaran Problem Solving Dengan Model Pembelajaran Jigsaw dalam Mempengaruhi Efektifitas Hasil Belajar Siswa Kelas VIII di SMPN 2 Keruak - Ittihad (Pendidikan Al-Gafari, 2024)
Education is provisions man in wade life in this world. Since the beginning man was born in the world has felt enjoyment of education, because, with provisions of education, man can build knowledge, expand insight, and shape his personality. Research purposes This is for a better comparison between Model Learning Problem Solving with Model Learning Jigsaw in increased results Study to students class VIII. Study this is a study experiment. The research design used is a Quasi-Experimental design (experiment pseudo) using the Pretest-posttest control group design model. Collection technique data with the use of documentation and tests. Population in study This is class VIII, and samples study This is class VIII C a class experiment for Learning Models Problem Solving, and class VIII B a class experiment for model learning Jigsaw, each class totaling 30 people. The analysis technique used for hypothesis testing is the t-test. The study results show that: (1) Model Learning Problem Solving effective in increasing results Study Social Sciences Integrated on student class VIII. With ????ℎ???????????????????? = 3.73, and ???????????????????????? = 2.04 with dk (30-1 = 29) at level significance 5%, So ????ℎ???????????????????? > ???????????????????????? namely 7.98 > 2.00, then ????o rejected or Ha accepted. (2) Model Learning Jigsaw No effective in increasing results Study Social Sciences Integrated on student class VIII. With mark ????ℎ???????????????????? =1.02 with level significance 5% (0.05) And et al = 29 so meet ???????????????????????? = 2.04, So ????ℎ???????????????????? < ???????????????????????? namely 1.02 < 2.04, then ????o accepted or Ha rejected. (3) Comparison Learning model Problem Solving with Models Learning Deep jigsaw increases results learning Integrated Social Sciences for students in class VIII. With ????ℎ???????????????????? = 7.98 and ???????????????????????? = 2.00 with level significance 5% (0.05) and dk (???? 1 + ???? 2 − 2 = 30 + 30 - 2) =58. So ????ℎ???????????????????? > ???????????????????????? namely 7.98 > 2.00, so Ho rejected or Ha accepted.